COMPARISON OF WORKPLACE BULLYING, DISTRESS LEVEL and SATISFACTION WITH LIFE: CROSS-SECTIONAL STUDY ON POWER PLANT ENERGY IN INDONESIA - Ika Agustina Wahyuningtias; Sjahrul Meizar Nasri; Dadan Erwandi; Fatma Lestari; Abdul Kadir (Universitas Pahlawan, 2021)
Introduction: Bullying does not only occur in the school environment. It can also happen at the workplace. There have been several definitions on bullying in the psychological literature but, in general, bullying is described as aggressive behavior by a person or group of people who feel more powerful, with the aim of hurting, humiliating, or isolating victims who feel helpless (Salmivalli, March–April 2010) (Gredler, 2003) Bullying can affect employee's satisfaction with life, which negatively relates to job satisfaction and mental health status of workers (Gabriele , et al., 2015). Work-related losses due to work accidents caused by fatigue triggered by workplace bullying will also increase if the psychosocial hazards caused by bullying are not managed properly and correctly (Young-Ran & Jeong-Won , 2016) (Rohit, et al., 2009) (Ma, et al., 2010). Research related to workplace bullying is still difficult to find in Indonesia, even the existing reports on this topic are barely enough to explain how this phenomenon is handled this country. Bullying has been widely researched, but the majority of the studies are performed in school settings or adolescent settings. There has not been any in-depth research on bullying that has been conducted comprehensively in work settings (Silviandari & Helmi, 2018). This study aims to determine and examine the incidence of workplace bullying in the energy sector or the power generation industry by involving seven power plants throughout Indonesia. Method: This was a cross-sectional study involving 219 workers in the power plant industry who were above 17 years of age and with a work experience of at least 6 months. These workers participated in this study by filling out the Negative Acts Questionnaire-Revised (NAQ-R). Results: The results of the analysis showed that there was no comparison of bullying incidents among the seven power plants (F = 0.71, p = 0.135) and that the bullying level in these 7 power plants was low (mean= 26.7), with the highest mean was found in Southeast Sulawesi (mean=27.9). Conclusion: This shows that the incidence of bullying in the seven power plants is in the low category, with the highest tendency of bullying seen in the power plant in Southeast Sulawesi.